Development of Ludo Game Learning Media for Social Studies Subjects in Grade IV of Napallicin Elementary School - Puspita, Intan; Samitra, Dian; Sujarwo, Sujarwo (Global Education Journal, 2025)
The purpose of this study was to develop a ludo game learning media in social studies subjects in grade IV of Napallicin State Elementary School. Testing the validity. Practicality, and effectiveness of the ludo game learning media in social studies subjects in grade IV of Napallicin State Elementary School. The method used in this study is the ADDIE Development method. This development research produces a valid, practical, and effective ludo game product, namely the validity of the learning media that has been developed is included in the "Valid" category with the Aiken'V coefficient determined based on the results of the ludo game media assessment by the three validators, namely language experts 0.92, material experts 0.95, and media experts 0.83. The practicality of the ludo game media shows an Aiken'V coefficient of 89% which is determined based on the results of the calculation of the practicality questionnaire of the responses given by students to the ludo game media. So that the ludo game in social studies subjects in grade IV of Napallicin State Elementary School is included in the "Very Practical" category. Ludo game media in social studies subjects in grade IV of SD Negeri Napallicin has an effect on student learning outcomes where only 2 students did not complete and 18 students were deferred with an average of 84.3% in the category "Very Effective". This media can help students and teachers in classroom learning, especially in the material of Norms in the customs of my region.